Исследование магнитного поля высоковольтных линий электропередачи переменного тока - Розов, В.Ю.; Реуцкий, С.Ю.; Пелевин, Д.Е.; Яковенко, В.М. (Технічна електродинаміка, 2012)
The mathematical model of the 50 Hz three-phase overhead power transmission line and the engineering method of the calculation of the root mean square value of the magnetic field density are developed on the base of Biot–Savart’s and Laplace’s equations. The results of the experimental verification of the method developed are presented. They have been carried out on three operating transmission lines with the voltage 330 kV. The data show that the method developed provides the acceptable precision of the calculation with the relative error less than 10% at the distance of more than 10 m from the line. It is shown that with the nominal current 2 kA the induction of the magnetic field is equal to 3,7 μT on the border of the transmission line protection zone (38 m). It decreases to the safe level of 0,5 μT at the distance of more than 100 m from the line. This raises the problem of the formation of the size of sanitary protection zones taking into account not only electrical field but also the magnetic field.